STREAMLINING REGULATORY DOCUMENTATION: EXPLORING THE COMMON TECHNICAL DOCUMENT (CTD) AND ELECTRONIC SUBMISSION, WITH EMPHASIS ON M SERIES ACCORDING TO ICH GUIDELINES - RASHYAP SARASWAT,; ANKITA RAIKWAR,; SUBHRANSHU PANDA, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
A number of regulatory bodies have worked together to create the Common Technical Document (CTD), including the United States Food and Drug Administration, the European Medicines Agency, and the Japanese Ministry of Health. This standardized format facilitates the collection and submission of regulatory documentation pertaining to applications for new medicines. Since its inception in 2000, the CTD has been widely adopted internationally, including by nations such as Canada, Australia, and India. The CTD aims to streamline the submission process, reduce duplication of effort, and facilitate regulatory evaluations by providing a uniform structure for technical documentation. This article outlines the guidelines and organization of the CTD, including its modules covering administrative information, quality, non-clinical studies, and clinical trials. The CTD’s significance lies in its ability to improve regulatory efficiency, promote data transparency, and expedite the availability of new medicines to patients. However, challenges persist, such as variations in regional requirements and the need for continued adaptation to evolving technological standards. Electronic submissions and improved information management are two ways in which the new electronic CTD (eCTD) has improved submission procedures. Despite some ongoing issues, the CTD and eCTD represent significant advancements in regulatory documentation, with the potential for further innovation and global adoption in the future.